Patients using antifungals following laryngectomy: a qualitative study of community pharmacists in the North of England. (13th September 2013) - Todd, Adam; Husband, Andrew K.; Hurren, Anne; Kler, Simran; Ling, Jonathan
Abstract Objective To explore community pharmacists' understanding and opinions in relation to the prevention of fungal colonisation of voice prostheses amongst laryngectomy patients. Method Semi‐structured interviews were conducted on a purposive sample of 12 community pharmacists from the North of England. Interviews were undertaken until data saturation was reached and responses were transcribed verbatim and analysed using a thematic approach. Key findings Six themes emerged from the data analysis. These were: terminology confusion about laryngectomy, stoma and voice prostheses; smoking as a risk factor for the development of laryngeal cancer; using nystatin to prevent biofilm formation; counselling information related to nystatin; prescription intervention and additional education in relation to laryngectomy. The theme of counselling information related to nystatin use and additional education was a key finding: our data show that when dispensing nystatin to patients with a voice prosthesis, community pharmacists would either give no advice related to medication use or would give incorrect advice that may lead to premature prosthesis failure amongst this patient group. Conclusion This study highlights that community pharmacists lack understanding in relation to laryngectomy and are unaware of the off‐label doses and administration methods of the drugs (specifically nystatin) used to prevent fungal colonisation on voice prostheses. Additional information sources in the form of an educational leaflet, possibly obtained through the local department of speech and language therapy, would be perceived as a valuable resource to support community pharmacists who are required to manage these patients in the community.